Social and Ethnic Segregation of Muslim community in Matara District, Sri Lanka - Gamachchige, R.N.; Thennakoon, T.M.S.P.K.; Thrimawithana, R.T. (My University, 2017)
Attached

This paper discusses the process and characteristics of social and ethnic segregation in Sri Lankan Muslim community. The research is aimed at analyzing the ethnic segregation of Muslim community in Matara district. A sample survey to investigate the segregation process and its characteristics was conducted in two DS divisions selected based on the index value and Muslim population density. The Study revealed that the causes of segregation were their higher birth rate and weak economic status which led to vertical segregation of Muslim community in Weligama and Welipitiya DS Divisions. The dissimilarity index, which is a primary statistical measurements of segregation provided evidence of a high Muslim segregation in Matara.
Keywords: Social and Ethnic segregation; Muslims; dissimilarity index; Matara